Formation and structure of V–Zr amorphous alloy thin films. (15th January 2015) - King, D.J.M.; Middleburgh, S.C.; Liu, A.C.Y.; Tahini, H.A.; Lumpkin, G.R.; Cortie, M.B.
Abstract: Although the equilibrium phase diagram predicts that alloys in the central part of the V–Zr system should consist of V2 Zr Laves phase with partial segregation of one element, it is known that under non-equilibrium conditions these materials can form amorphous structures. Here we examine the structures and stabilities of thin film V–Zr alloys deposited at room temperature by magnetron sputtering. The films were characterized by X-ray diffraction, transmission electron microscopy and computational methods. Atomic-scale modelling was used to investigate the enthalpies of formation of the various competing structures. The calculations confirmed that an amorphous solid solution would be significantly more stable than a random body-centred solid solution of the elements, in agreement with the experimental results. In addition, the modelling effort provided insight into the probable atomic configurations of the amorphous structures allowing predictions of the average distance to the first and second nearest neighbours in the system.